Pengaruh Ukuran Perusahaan, Nilai Saham, Financial Leverage, Profitabilitas Pada Tindakan Perataan Laba di Sektor Manufaktur - Pradnyandari, A. A. Istri Rani; Putra Astika, Ida Bagus (E-Jurnal Akuntansi, 2019)
This study aims to examine the effect of company size, stock value, financial leverage, and profitability on income smoothing policies in the manufacturing sector in the Indonesia Stock Exchange for the 2014-2016 period. The number of samples, using the purposive sampling method is as many as 40 companies from 147 companies. The data analysis technique is logistic analysis with the results of company size having a positive effect on income smoothing in the manufacturing sector. The value of shares has a negative effect on income smoothing in the manufacturing sector. Financial leverage has a positive effect on income smoothing in the manufacturing sector. Profitability has a positive effect on income smoothing in the manufacturing sector. Sectoral manufacturing companies are expected to pay attention to the size of the company, so the company chooses to do income smoothing. Keywords : Company size, stock value, financial leverage, profitability, income smoothing policy